La normativa hispano medieval y su aplicación en Indias : condición femenina dentro del marco penal y procesal (Estudios de Historia de España, 2016)
The exchanged of cultures during the residence of the new settlers on American soil resulted in the implementation of different rules from the medieval Hispania, but also a serious imbalance in the application of these practices for women of different social status. Sometimes indigenous, mestizo and Spanish were able to achieve flexible positions –from the canon and civil authorities– at the time of being fined or punished by the law, other times, his weigth fell to the fullest extend without regard to any type of differentiation among women.
Keywords: Women’s History; Middle Ages; Conquest of America; Medieval Law; Royal Charters